2019
DOI: 10.11648/j.ijnfs.20190803.11
|View full text |Cite
|
Sign up to set email alerts
|

Study the Relation Between Acetylcholinesterase and Obesity in University Students

Abstract: Obesity is described as an asymmetrical body weight for height with an extreme growth of adipose tissue that is usually with the highest risk of disordered lipid profile. Obesity is caused by a sequence of excessive food intake, absence of physical motion, and hereditary predisposition. A few instances are caused primarily by genes, endocrine dysfunctions, medicines, or mental confusion. BMI gives a simple numeric test of obesity. BMIs below 20.0kg/m 2 and above 25.0kg/m 2 has been connected with significant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The present studies metals showed results more than normal range except Mg, Co, Cu, Zn are within the normal range, but Fe results are less than normal range in all studied groups. These results may be due to the effect of lifestyle and environmental pollution and toxicity, including water, air, and food [6][7][8][9]. Some lighter metals and metalloids are poisonous and, thus, are named heavy metals though some heavy metals, such as gold, are not toxic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present studies metals showed results more than normal range except Mg, Co, Cu, Zn are within the normal range, but Fe results are less than normal range in all studied groups. These results may be due to the effect of lifestyle and environmental pollution and toxicity, including water, air, and food [6][7][8][9]. Some lighter metals and metalloids are poisonous and, thus, are named heavy metals though some heavy metals, such as gold, are not toxic.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol approved by The student's weights and heights were included on a single calibrated scale (SR Scales, SR Instruments). The formula calculated body mass index (BMI): weight in kilograms (kg) divided by height in square meters (m 2 ) [1,[5][6][7][8][9].…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed the level of acetylcholinesterase (AChE) in the serum samples according to our previous publication [ 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. We determined the activity of AChE with the kinetic colorimetric method according to Deutsche (1992) with the ARCHITECT systems [ 87 ].…”
Section: Methodsmentioning
confidence: 99%